Repeated α-GalCer Administration Induces a Type 2 Cytokine-Biased iNKT Cell Response and Exacerbates Atopic Skin Inflammation in Vα14Tg NC/Nga Mice - Hyun Jung Park (MDPI AG, 2021)
We have previously shown that Vα14 TCR Tg (Vα14Tg) NC/Nga (NC) mice contain increased numbers of double-negative (DN) invariant natural killer T (iNKT) cells that protect against spontaneous development of atopic dermatitis (AD). iNKT cells can regulate immune responses by producing various cytokines such as IFNγ and IL4 rapidly upon stimulation with α-galactosylceramide (α-GalCer), a prototypical iNKT cell agonist. However, the precise role of α-GalCer-activated iNKT cells in AD development remains unclear. Therefore, we examined whether repeated activation of iNKT cells with α-GalCer can regulate the pathogenesis of AD in Vα14Tg NC mice. We found that Vα14Tg NC mice injected repeatedly with α-GalCer display exacerbated AD symptoms (e.g., a higher clinical score, IgE hyperproduction, and increased numbers of splenic mast cells and neutrophils) compared with vehicle-injected Vα14Tg NC mice. Moreover, the severity of AD pathogenesis in α-GalCer-injected Vα14Tg NC mice correlated with increased Th2 cells but reduced Th1 and Foxp3+ Treg cells. Furthermore, the resulting alterations in the Th1/Th2 and Treg/Th2 balance were strongly associated with a biased expansion of type 2 cytokine-deviated iNKT cells in α-GalCer-treated Vα14Tg NC mice. Collectively, our results have demonstrated the adverse effect of repeated α-GalCer treatment on skin inflammation mediated by type 2 immunity.